2001
DOI: 10.1046/j.1365-2168.2001.01745.x
|View full text |Cite
|
Sign up to set email alerts
|

Fate of hypertension after repair of coarctation of the aorta in adults

Abstract: Surgical repair of coarctation of the aorta in adults leads to regression of systolic hypertension and a decreased requirement for antihypertensive medication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 12 publications
1
17
0
1
Order By: Relevance
“…A similar study by Bhat et al [37] on 84 patients concluded identical implications. However, some patients developed hypertension late after successful surgical repair of aortic coarctation.…”
Section: Congenital Heart Defectssupporting
confidence: 68%
“…A similar study by Bhat et al [37] on 84 patients concluded identical implications. However, some patients developed hypertension late after successful surgical repair of aortic coarctation.…”
Section: Congenital Heart Defectssupporting
confidence: 68%
“…Following interventional treatment that resulted in a correction of the anatomical stenosis, hypertension persists or develops after a period of normotension in about 32.5% (25-68%) of patients. In a large proportion of patient, exercise-induced hypertension may be diagnosed based on an exercise test [74][75][76][77].…”
Section: Hypertension In Children After Surgical Treatment Of Coarctamentioning
confidence: 99%
“…Seven of the patients continued to have systolic hypertension, and 14 were taking antihypertensive medication. The outcome in terms of blood pressure after stent implantation seems to be comparable with that after surgical repair of coarctation in adults [40,41].…”
Section: Blood Pressure After Stent Implantation For Coarctationmentioning
confidence: 70%